2003
DOI: 10.1128/jvi.77.22.12067-12073.2003
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-Induced Immunopathology during Bovine Respiratory Syncytial Virus Infection: Exploring the Parameters of Pathogenesis

Abstract: The bovine and human respiratory syncytial viruses cause severe lower respiratory tract infections. Effective vaccines against the respiratory syncytial viruses have been lacking since vaccine failures in the 1960s and 1970s. In this report, we describe a bovine respiratory syncytial virus (bRSV) challenge model in which both classical bRSV respiratory infection and vaccine-enhanced immune pathology were reproduced. The classical, formalin-inactivated (FI) bRSV vaccine that has been associated with vaccine fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
88
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 26 publications
5
88
1
Order By: Relevance
“…Vaccination and challenge experiments have been described in detail previously [1]. Briefly, bRSV was cultured on embryonic bovine trachea (EBTr) cells.…”
Section: Viruses and Animalsmentioning
confidence: 99%
See 4 more Smart Citations
“…Vaccination and challenge experiments have been described in detail previously [1]. Briefly, bRSV was cultured on embryonic bovine trachea (EBTr) cells.…”
Section: Viruses and Animalsmentioning
confidence: 99%
“…This phenomenon was first observed in a human vaccine trial in the 1960s [4] and was later found to also occur in cattle immunized with formalin-or beta-propriolactone-inactivated bRSV [5,6]. Enhanced disease resulting from immunization with Fl-virus has an immunopathological basis and has now been modeled in hRSV-infected mice [2,[7][8][9] and monkeys [10] and in bRSV-infected cattle [1,[11][12][13]. In mice, immunization with inactivated virus evokes a Th-2 biased CD4 T cell response, which is associated with eosinophilia and clinical symptoms upon challenge [2].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations